ChemInform Abstract: Ceric Ammonium Nitrate (CAN) Catalyzed Modification of Ketones via Two C—C Bond Cleavages with the Retention of the Oxo‐Group. Issue 50 (16th December 2014) - Feng, Peng; Sun, Xiang; Su, Yijin; Li, Xinyao; Zhang, Li‐He; Shi, Xiaodong; Jiao, Ning
Abstract The optimized procedure can be applied to various aryl ketones and best results concerning the yields are obtained with a second keto group at the β‐position of the substrate.